Association between classic and specific bioimpedance vector analysis and sarcopenia in older adults: a cross-sectional study - Ana Claudia Rossini-Venturini; Pedro Pugliesi Abdalla; Priscila Giacomo Fassini; André Pereira dos Santos; Márcio Fernando Tasinafo Junior; Thiago Cândido Alves; Euripedes Barsanulfo Gonçalves Gomide; Tatiane Lopes de Pontes; Karina Pfrimer; Eduardo Ferriolli; Jorge Mota; Maria Reyes Beltran-Valls; et al. (BMC, 2022)
Abstract Background To verify (1) the association between classic and specific bioelectrical impedance vector analysis (BIVA) with body composition, hydration, and physical performance in older adults with and without sarcopenia; (2) which BIVA most accurately distinguishes sarcopenia. Methods A sample of 94 older adults with and without sarcopenia (29 men and 65 women, 60-85 years) was evaluated. The classic and specific BIVA procedures, Dual energy X-ray absorptiometry (DXA), and deuterium dilution were performed. Sarcopenia was defined by muscle weakness and low skeletal muscle index, while severity was indicated by low physical performance. Results The BIVA's potential to monitor hydration and muscle mass loss in older adults seems feasible. Classic and specific BIVA were able to distinguish sarcopenia in women (p < 0.001), but not in men. When the sarcopenia criteria were individually analyzed, both classic and specific BIVA were able to distinguish low skeletal muscle index in women, while only classic BIVA did for men. For the criterion of slow physical performance, only the classic BIVA showed severity differences for women. The vectors of adults without sarcopenia of both sexes tended to be positioned in the left region of the ellipses, revealing a predominance of soft tissues. Conclusions Classic BIVA has a distinct sarcopenic association with body composition, hydration, and physical performance in older adults, while specific BIVA was similar between groups. Both BIVAs are sensible to detect female morphological changes (skeletal muscle index) but not for functional (handgrip, 6-min walk test) sarcopenia criteria. These procedures are promising tools for monitoring sarcopenia risks during aging.